Geographical Science as Precondition of Foming School Geographical Education in Ukraine - Inna Shorobura; Olesia Dolynska (Pedagogical Discourse, 2014)
Development of geographical science, as a precondition of forming school geographical education in Ukraine has been analyzed in the article. Economic and cultural prosperity of the countries stimulated development of geographical science. This, in its turn, provoked increased interest to the knowledge and researches of geographic peculiarities of different territories, their agricultural and industrial potential. Development of industry demanded study of resources of raw materials, expanding geological researches. Geography, from the set of varied data about separate countries, their geographical position and natural conditions, changes into the system of scientific knowledge, which favours formation of school geographical education in Ukraine.